Diseño de un aerogenerador para zona rural del Sumapaz, Cundinamarca (2016)
This project is focused on the design of a wind turbine for the rural area of Sumapaz, which involves the implementation of a series of events starting with the analysis of the availability of wind in the region of Sumapaz Paramo; then the study area, where energy demand cover and other external Factors that may be required as is the fauna and flora of the region was collected was performed. By having this information collected, we continued with the development of the machine, evaluating three possible solutions, but considering the most appropriate for the area. Next, the detailed design of the machine, in which calculations of all internal and external devices that require the machine to operate, among them are the three blades and type N4500 profiles were performed, developed the system multiplication it consists of two stages of planetary gears, the stepped shafts, electromagnetic brakes, braced tower, bolts, chassis and the main turbine hub.